Analysis of static and dynamic deformation modulus. Issue 2 (2nd April 2016) - Mikolainis, Mindaugas; Ustinovičius, Marijus; Sližytė, Danutė; Zhilkina, Tatyana
Abstract: This article summarises dynamic deformation modulus correlation with second reload of static plate load test results for an even thickness soil strata layer. An analysis of execution and result interpretation of both static deformation modulus and dynamic deformation modulus is provided also. Different correlations between the two modulus according to different authors are provided. Since dynamic plate load test is not regulated in Lithuania as a soil compaction contron method, a few dynamic plate load tests and static plate load tests were executed in order to compare compaction results. The additional experiments for dynamic plate load tests in different depths were executed which showed that deformation modulus is dependant on depth of test execution, thus it is worthwile to mention to be cautious on compaction results in trenches.